2002
DOI: 10.1159/000048354
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Cavernous Angiomas of the Spinal Cord in the Pediatric Age Group: A Pediatric Series

Abstract: The authors have reviewed available data from 7 pediatric patients with intramedullary spinal cord cavernous angioma (ISCCA) reported in the literature, and added from their own series 2 pediatric patients, for a total of 9 patients. This group of pediatric patients’ clinical presentation, course, management and outcome were compared to their adult counterparts as reported in the literature. In contrast to adults, children with symptomatic ISCCA do not show a gender imbalance and the thoracic spinal cord is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 37 publications
2
61
2
2
Order By: Relevance
“…Intramedullary cavernous malformations of the spinal cord are very uncommon, especially in children where only ten cases have yet been reported, mostly as isolated cases [1,3,6,14,17]. In 2002, Nagib and O'Fallon [14] summarized nine cases including their two personal cases, and in 2006, Bakir et al [3] reported another pediatric patient with ImCA: Although the number of reported pediatric cases with ImCA is small, we can outline some differences from that of the While ImCA in the adult occur more frequently in women than in men [12,17], with a female/male ratio of approximately 2:1, seven of ten cases of symptomatic ImCA reported in children were male, thus accounting for a male/ female ratio of 2:1.…”
Section: Special Features Of Imca In Childrenmentioning
confidence: 99%
See 4 more Smart Citations
“…Intramedullary cavernous malformations of the spinal cord are very uncommon, especially in children where only ten cases have yet been reported, mostly as isolated cases [1,3,6,14,17]. In 2002, Nagib and O'Fallon [14] summarized nine cases including their two personal cases, and in 2006, Bakir et al [3] reported another pediatric patient with ImCA: Although the number of reported pediatric cases with ImCA is small, we can outline some differences from that of the While ImCA in the adult occur more frequently in women than in men [12,17], with a female/male ratio of approximately 2:1, seven of ten cases of symptomatic ImCA reported in children were male, thus accounting for a male/ female ratio of 2:1.…”
Section: Special Features Of Imca In Childrenmentioning
confidence: 99%
“…In 2002, Nagib and O'Fallon [14] summarized nine cases including their two personal cases, and in 2006, Bakir et al [3] reported another pediatric patient with ImCA: Although the number of reported pediatric cases with ImCA is small, we can outline some differences from that of the While ImCA in the adult occur more frequently in women than in men [12,17], with a female/male ratio of approximately 2:1, seven of ten cases of symptomatic ImCA reported in children were male, thus accounting for a male/ female ratio of 2:1. The hypothesis of a hormonal effect leading to a greater risk of bleeding in female adults does not seem to be verified in children, but the mean age at bleeding is 13.2 years (range [8][9][10][11][12][13][14][15][16][17] and can also suggest the hormonal influence of puberty.…”
Section: Special Features Of Imca In Childrenmentioning
confidence: 99%
See 3 more Smart Citations